Visible Light-Driven Direct Z-Scheme Ho2SmSbO7/YbDyBiNbO7 Heterojunction Photocatalyst for Efficient Degradation of Fenitrothion - Liang Hao; Jingfei Luan (Molecules)
A highly versatile Z-scheme heterostructure, Ho2SmSbO7/YbDyBiNbO7 (HYO), was synthesized using an ultrasonic-assisted solvent thermal method. The HYO heterojunction, composed of dual A2B2O7 compounds, exhibits superior separation of photogenerated carriers due to its efficient Z-scheme mechanism. The synergistic properties of Ho2SmSbO7 and YbDyBiNbO7, particularly the excellent visible light absorption, enable HYO to achieve exceptional photocatalytic performance in the degradation of fenitrothion (FNT). Specifically, HYO demonstrated an outstanding removal efficiency of 99.83% for FNT and a mineralization rate of 98.77% for total organic carbon (TOC) during the degradation process. Comparative analyses revealed that HYO significantly outperformed other photocatalysts, including Ho2SmSbO7, YbDyBiNbO7, and N-doped TiO2, achieving removal rates that were 1.10, 1.20, and 2.97 times higher for FNT, respectively. For TOC mineralization, HYO exhibited even greater enhancements, with rates 1.13, 1.26, and 3.37 times higher than those of the aforementioned catalysts. Additionally, the stability and durability of HYO were systematically evaluated, confirming its potential applicability in practical scenarios. Trapping experiments and electron paramagnetic resonance analyses were conducted to identify the active species generated by HYO, specifically hydroxyl radicals (•OH), superoxide anions (•O2−), and holes (h+). This facilitated a comprehensive understanding of the degradation mechanisms and pathways associated with FNT. In conclusion, this study represents a substantial contribution to the advancement of efficient Z-scheme heterostructure and offers critical insights for the development of sustainable remediation approaches aimed at mitigating FNT contamination.